Technology Integration in Classroom Instruction and Its Influence on Student Engagement and Academic Achievement in Secondary Education. - Masa Sylvester Motadi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The integration of digital technologies into classroom instruction has become a defining feature of contemporary secondary education. Schools increasingly adopt digital tools, smart classrooms and technology-supported learning platforms to enhance teaching practices and improve student learning outcomes. This study examines how technology integration in classroom instruction influences student engagement and academic achievement in secondary education. The research adopted a qualitative secondary research design based on the systematic analysis of peer-reviewed studies published between 2020 and 2025. Ten empirical studies focusing on technology-enhanced learning environments, teacher digital competence and student engagement were analysed using thematic synthesis. The analysis identified five major themes: technology-supported student engagement, teacher digital competence and pedagogical mediation, smart classrooms and digital learning environments, technology integration and learning outcomes, and learner agency and self-regulated learning. The results show that technology can enhance behavioural, cognitive and motivational engagement when it is integrated into meaningful learning activities. The findings also reveal that the effectiveness of classroom technology depends strongly on teachers’ digital competence, classroom interaction and student-centred instructional approaches. Furthermore, technology-supported learning environments appear to contribute to academic achievement, collaboration and the development of digital competencies when learners actively participate in the learning process. The study concludes that the impact of technology integration in secondary education depends less on the presence of digital devices and more on the quality of pedagogy, teacher support and learner engagement within technology-enhanced classrooms.